2013
DOI: 10.19173/irrodl.v14i4.1573
|View full text |Cite
|
Sign up to set email alerts
|

Measuring use and creation of open educational resources in higher education

Abstract: The open educational resources initiative has been underway for over a decade now and higher education institutions are slowly adopting open educational resources (OER).The use and creation of OER are important aspects of adoption and both are needed for the benefits of OER to be fully realized. Based on the results of a survey developed to measure the readiness of faculty and staff to adopt OER, this paper focuses on the measurement of OER use and creation, and identifies factors to increase both. The survey … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
40
0
9

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 79 publications
(54 citation statements)
references
References 3 publications
1
40
0
9
Order By: Relevance
“…Despite its numerous advantages, OER are still in the early adoption stage (Mc Kerlich at al., 2013), which calls for a discussion on factors slowing the spread of their usage. Research has shown that a wider acceptance of OERs requires development of awareness and reaching an understanding of all their dimensions, increase of recognisability of the OER repositories, ensuring quality of content and development of online collaborative communities (Torres, 2013;Grodecka, Sliwowski, 2014;Mc Kerlich at al., 2013;Rolfe, 2012;Kortemeyer, 2013).…”
Section: Limitation Of Open Educational Resourcesmentioning
confidence: 99%
“…Despite its numerous advantages, OER are still in the early adoption stage (Mc Kerlich at al., 2013), which calls for a discussion on factors slowing the spread of their usage. Research has shown that a wider acceptance of OERs requires development of awareness and reaching an understanding of all their dimensions, increase of recognisability of the OER repositories, ensuring quality of content and development of online collaborative communities (Torres, 2013;Grodecka, Sliwowski, 2014;Mc Kerlich at al., 2013;Rolfe, 2012;Kortemeyer, 2013).…”
Section: Limitation Of Open Educational Resourcesmentioning
confidence: 99%
“…Utilized in the classroom, OER can provide powerful tools for teaching and learning. Studies indicate that a growing number of OER are becoming available for use in the classroom (McKerlich, et al, 2013). Limited research has been done regarding the efficacy of using OER instead of traditional resources.…”
Section: Describes How Washingtonmentioning
confidence: 99%
“…There is a real possibility that publishers and journals from poor, underdeveloped and developing countries be unfairly compared with those from developed countries. It means that high criteria from highly developed countries are also applied for developing countries creating comparison bias [45,46]. Therefore, recommendations given for hijacked journals cannot be entirely applied to predatory publishers and/or journals.…”
Section: Discussionmentioning
confidence: 99%